2015
DOI: 10.1002/nme.4918
|View full text |Cite
|
Sign up to set email alerts
|

The weak substitution method – an application of the mortar method for patch coupling in NURBS‐based isogeometric analysis

Abstract: In this contribution, a mortar-type method for the coupling of non-conforming NURBS (Non-Uniform Rational B-spline) surface patches is proposed. The connection of non-conforming patches with shared degrees of freedom requires mutual refinement, which propagates throughout the whole patch due to the tensor-product structure of NURBS surfaces. Thus, methods to handle non-conforming meshes are essential in NURBSbased isogeometric analysis. The main objective of this work is to provide a simple and efficient way t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 28 publications
2
61
0
Order By: Relevance
“…dual shape functions with an extended support [33,50]. Nonetheless, the presented method provides an easy and efficient way of coupling patches without increasing the global system size (compared to [33]) and gaining a localization of the coupling (compared to [32]). …”
Section: -Dimensional Tied Contact: Convergence Studymentioning
confidence: 99%
See 1 more Smart Citation
“…dual shape functions with an extended support [33,50]. Nonetheless, the presented method provides an easy and efficient way of coupling patches without increasing the global system size (compared to [33]) and gaining a localization of the coupling (compared to [32]). …”
Section: -Dimensional Tied Contact: Convergence Studymentioning
confidence: 99%
“…A comprehensive review on dual mortar methods for contact mechanics can be found in [28,29]. In the context of domain decomposition in IGA, optimality and stability of standard mortar methods have only very recently been investigated in [30][31][32][33], where also the construction of dual B-spline basis functions has been outlined theoretically [33].…”
Section: Introductionmentioning
confidence: 99%
“…Although it appears interesting because of the strong mathematics behind it and the absence of additional degrees of freedom, the Nitsche method leads to considerable implementation work and an increased cost of computation, since an additional eigenvalue problem has to be solved for the stabilizing term. As a result, Dornisch et al [26] has recently developed a weak substitution method that can be interpreted as a mortar method. Although the combination of the FCM with Nitsche coupling may be promising, the drawback of such a strategy, if directly applied to the local enrichment of a NURBS patch, is that it suffers from some intrusiveness.…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast with the more usual situation of the coupling of IGA patches which is achieved along C 0 interfaces (see, e.g., [11,25,26,29,30]). …”
Section: Governing Equationsmentioning
confidence: 69%
“…Even if it may appear interesting due to the absence of additional degrees of freedom, the Nitsche method leads to a comparatively high computational effort since an additional eigenvalue problem has to be solved for the stabilizing term. As a result, Dornisch et al [30] developed a weak substitution method to simplify the implementation and reduce the computational cost. From this overview, it may be noticed that most of the coupling techniques elaborated for NURBS nowadays are dedicated to the connection of NURBS patches, i.e., the coupling along a C 0 interface.…”
Section: Introductionmentioning
confidence: 99%